Metamorphosis: Change & Continuity, Chaos & Order, Conflict & Transformation - Halligan, Fredrica R. (Journal of religion and health, 2004)
Metamorphosis is an organic process of change that is seen in all levels of life. Whether at the individual, the corporate or the global level of human life, the processes of change involve natural periods of chaos and order, times of conflict that underlie the movement toward transformation, and developmental shifts that may be painful as well as pleasurable. This paper addresses these phenomena in relation to current changes going on in our world.